Juan José Martinena Ruiz - Segura Urra, Félix (Huarte de San Juan. Geografía e Historia, 2014)
The article reviews the biography of Juan José Martinena (Pamplona, 1949), director of the Royal and General Archive of Navarre since 1985 until his retirement in 2010. Doctor’s degree in history, he has cultivated several disciplines such as heraldry, castellology, archival science and history; and he is also the author of a large number of articles and monographs, most of them devoted to the Navarrese history, and particularly, the history of Pamplona. His best-known side is as a disseminator and expert partner of several media, mainly press, but also radio and television stations.
Keywords: Biography; Archivist; Historian; Navarre; Pamplona